Rewards in Early Childhood Classroom: Short-Term Gains, Long-Term Costs? - Sari, Maulida; Amalia, Rizka (Jurusan Pendidikan Islam Anak Usia Dini, 2025)
The use of rewards as a motivational strategy has long been applied in education, but its effectiveness and impact on children's intrinsic motivation are still crucial debates. Therefore, this study aims to analyze the meaning of rewards in increasing early childhood learning motivation in Islamic Kindergartens, and to understand its implications for educational practices Initial observations at TK Anak Islam indicate the existence of diverse reward-giving practices, but an in-depth understanding of children's perceptions and the effectiveness of rewards in triggering sustainable motivation is still limited. The method used in this study was qualitative-descriptive, with the aim of understanding how rewards are interpreted and how they influence learning motivation in early childhood. The study was conducted at TK Anak Islam, which implements a reward-based learning system to increase learning motivation in early childhood. The results of the study identified four main types of rewards: material (stickers, stationery), social (verbal praise, applause), activity/privilege (opportunity to choose, additional playtime), and symbolic (achievement cards, star boards). Verbal praise is the form most often used and considered effective by teachers.Research recommendations emphasize the importance of reward variation, consistency, timely delivery, and a focus on the child's effort process in reward-giving strategies.